-9=6h+2h+7

Simple and best practice solution for -9=6h+2h+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9=6h+2h+7 equation:


Simplifying
-9 = 6h + 2h + 7

Reorder the terms:
-9 = 7 + 6h + 2h

Combine like terms: 6h + 2h = 8h
-9 = 7 + 8h

Solving
-9 = 7 + 8h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-8h' to each side of the equation.
-9 + -8h = 7 + 8h + -8h

Combine like terms: 8h + -8h = 0
-9 + -8h = 7 + 0
-9 + -8h = 7

Add '9' to each side of the equation.
-9 + 9 + -8h = 7 + 9

Combine like terms: -9 + 9 = 0
0 + -8h = 7 + 9
-8h = 7 + 9

Combine like terms: 7 + 9 = 16
-8h = 16

Divide each side by '-8'.
h = -2

Simplifying
h = -2

See similar equations:

| x+(2x-1)+(3x-4)=27 | | 9x-49=0 | | 4ln(5x)=8 | | 2m^2+16m+30=0 | | 11=k+4 | | -2(6t+8)= | | 5x+8=5x+7 | | 5z-2=3z+5 | | 20-8x+30-8x=180 | | (X+5)-(4x-1)=0 | | 9-x+3x-2-9x= | | 15a=-5a+10 | | 4*(X-2)=4+2*(X-1) | | 6m=24+x | | 140s*20s= | | 6+2y+y=12 | | 8m-3m=15 | | 8x^2+5y^2=40 | | 2x+37=8x+7 | | 8x-12=4x+20 | | x=y^2-5 | | 3y+4=5y-6 | | 5x^2+2y^2=10 | | 5*(m+1)-3*(2m+1)=4*(5-m) | | 3m=7m-16 | | x+487-69=3865 | | p(x)=80-3x | | X+9=8x^2+16 | | -30u+(-6u)= | | 8x^2+16x= | | 2x+4x+40=180 | | 2(y-1)+4y=8 |

Equations solver categories